Chinese expert consensus on the diagnosis and treatment of HER2‐altered non–small cell lung cancer. Issue 1 (28th November 2022) - Zhang, Shirong; Wang, Wenxian; Xu, Chunwei; Zhang, Yongchang; Cai, Xiuyu; Wang, Qian; Song, Zhengbo; Li, Ziming; Yu, Jinpu; Zhong, Wenzhao; Wang, Zhijie; Liu, Jingjing; et al.
Abstract: Human epidermal growth factor receptor 2 (HER2) possesses tyrosine kinase activity and participates in cell growth, differentiation and migration, and survival. Its alterations, mainly including mutations, amplifications, and overexpression are associated with poor prognosis and are one of the major drivers in non–small cell lung cancer (NSCLC). Several clinical trials had been investigating on the treatments of HER2‐altered NSCLC, including conventional chemotherapy, programmed death 1 (PD‐1) inhibitors, tyrosine kinase inhibitors (TKIs) and antibody‐drug conjugates (ADCs), however, the results were either disappointing or encouraging, but inconsistent. Trastuzumab deruxtecan (T‐DXd) was recently approved by the Food and Drug Administration as the first targeted agent for treating HER2 ‐mutant NSCLC. Effective screening of patients is the key to the clinical application of HER2‐targeted agents such as TKIs and ADCs. Various testing methods are nowadays available, including polymerase chain reaction (PCR), next‐generation sequencing (NGS), fluorescence in situ hybridization (FISH), immunohistochemistry (IHC), etc. Each method has its pros and cons and should be reasonably assigned to appropriate patients for diagnosis and guiding treatment decisions. To help standardize the clinical workflow, our expert group reached a consensus on the clinical management of HER2‐altered NSCLC, focusing on the diagnosis and treatment strategies. Abstract : To improve the diagnosis and treatment of HER2‐altered non‐small cell lung cancer in China, we reached consensus on detection strategy based on alteration type, sample selection, detection method, quality control, and treatment suggestion. Moreover, we systematically reviewed the clinical efficacy, resistance mechanisms, and development status of HER2‐ targeting drugs.